Adenoid Squamous Cell Carcinoma of Oral Cavity: a Case Report - Chandrakala Jayani; Sahana Srinath; Girish Giraddi; Rohit Kumar Kendole (Shiraz University of Medical Sciences, 2018)
Adenoid squamous cell carcinoma is a rare variant of squamous cell carcinoma with features of adenoid pattern. It has been reported to originate in the sun- exposed skin of the head and neck region. Although rare, there are cases documented within the oral cavity and nasopharynx. The clinical behaviour and the prognosis are variable. We report a case of adenoid squamous cell carcinoma in a 63-year-old female patient presented with a large mass in the left mandibular alveolar ridge. Histologically, the lesion showed areas of conventional squamous cell carcinoma along with atypical epithelial cells forming a glandular pattern. However, there is no evidence of glandular differentiation, secretory activity or its products. Adenoid squamous cell carcinoma must be differentiated from adenosquamous carcinoma in which adenocarcinoma elements are positive for mucins. There are few cases reported to establish biological behaviour and prognosis.